A DCA‐based sparse coding for video summarization with MCP. Issue 5 (5th January 2023) - Li, Yujie; Li, Zhenni; Tan, Benying; Ding, Shuxue
Abstract: Video summarization offers a summary version that conveys the primary information of a longer video. The main challenges of video summarization are related to keyframe extraction and saliency mapping. Thus, this work proposes a sparse coding model for keyframe extraction and saliency mapping applications. Specifically, the minimax concave penalty (MCP) is utilized as a sparse regularization scheme and the regularized non‐convex MCP problem is solved by decomposing MCP into two convex functions and the convex function's algorithm difference is relied on to solve the resulting sub‐problems. The experimental results demonstrate higher compressed keyframes and saliency maps than current state‐of‐the‐art algorithms. In particular, the model attains a lower summary length of 34% and 19% compared to sparse modeling representation selection (SMRS) and sparse modeling using the determinant sparsity measure (SC‐det), respectively. In addition, the developed scheme has a shorter computation time, requiring 82% and 33% less time than the ITTI and the dense and sparse reconstruction (DSR) methods. Abstract : We propose a sparse coding model with MCP for keyframe extraction and saliency mapping applications. Specifically, we utilize MCP as a sparse regularization scheme and solve the regularized non‐convex MCP problem by decomposing MCP into two convex functions and rely on the convex function's algorithm difference to solve the resulting sub‐problems.